Penerapan Sistem Evaluasi Belajar Dalam Meningkatkan Kualitas Sekolah Bagi Siswa Kelas IX A di MTs Ma’arif Gondang - Achmad Subhi Amirul Hakim; Robingun Suyud El Syam; Ali Imron (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This paper aims to describe the application of the learning evaluation system in improving school quality for class IX A students at MTs Ma'arif Gondang. The research is descriptive qualitative research, with qualitative analysis. The research results show that the evaluation of the learning implementation process carried out includes the suitability between the learning process and the learning implementation plan (RPP), the readiness of teachers and students in the learning activities carried out in the classroom. Student participation also plays an important role in learning activities as well as communication carried out by teachers to get feedback from students during the learning process. Providing motivation to students in the learning process is important to increase students' enthusiasm for learning. Students' mastery and desire for specific goals that will be achieved in learning activities. Learning evaluation also includes assessment aspects which include the domains of attitudes, knowledge and skills. The learning evaluation system implemented at MTs Ma'arif Gondang can improve the quality of the school based on the results of the questionnaire obtained in the very good category.